Preparation method and application of a heterogeneous photocatalyst

CN118454725BActive Publication Date: 2026-10-30NANCHANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410670043.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2026-10-30
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

然而,目前阴离子和阳离子双空位诱导的空间分离助催化剂在光催化还原U(VI)反应体系中的促进作用机制尚不清楚

Benefits of technology

(1)本发明合成的多相Ti3C2Tx基光催化剂,方法简便、结构清晰及稳定性好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118454725B_ABST
    Figure CN118454725B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a multi-phase photocatalyst and belongs to the technical field of environmental protection. x MXene is mixed, N vacancies and Ti vacancies are generated through N2 thermal etching, and then the multi-phase Ti3C2T x is coupled with MnO x to prepare a multi-phase Ti3C2T x -based photocatalyst. The multi-phase Ti3C2T -based photocatalyst prepared by the application has the characteristics of high charge space separation efficiency, fast charge transfer rate, good selectivity, strong photocatalytic reduction U(VI) capacity and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental protection technology, specifically to a method for preparing and applying a multiphase photocatalyst. Background Technology

[0002] Hydrometallurgical processes involving lanthanides typically generate large quantities of waste residue and residual solutions containing radioactive uranium, posing irreversible risks to human health and the environment. To date, reducing soluble and free-flowing U(VI) to insoluble U(IV) using various strategies is a promising U(VI) removal technology. Among these, semiconductor photocatalytic reduction is characterized by its green efficiency, low cost, and low secondary pollution (L. Feng, Y. Yuan, B. Yan, T. Feng, Y. Jian, J. Zhang, W. Sun, K. Lin, G. Luo, N. Wang, Halogen hydrogen-bonded organic framework (XHOF) constructed by singlet open-shell diradical for efficient photoreduction of U(VI), Nat. Commun., 13 (2022) 1389). Various semiconductor photocatalysts possess the ability to photocatalytically reduce U(VI), but factors such as low solar energy utilization, high photogenerated carrier recombination rates, and a lack of sufficient U(VI) adsorption sites inhibit their overall photocatalytic efficiency. In addition, the limited U(VI) active sites on most photocatalysts are easily covered by uranium precipitated after photoreduction, or U(IV) is easily re-oxidized due to the closure of U(VI) redox active sites in the photocatalyst (P. He, L. Zhang, L. Wu, S. Xiao, X. Ren, R. He, X. Yang, R. Liu, T. Duan, Synergy of oxygen vacancies and thermoelectric effectenhances uranium(VI) photoreduction, Appl. Catal. B: Environ., 322 (2023)122087).

[0003] Surface defect engineering has become an effective strategy for overcoming the aforementioned challenges. It allows for the modulation of photocatalyst photoelectric parameters and active sites by controlling electronic structure, local surface microstructure, and carrier concentration. Metal vacancies are shallow acceptors that promote p-type semiconductors, while anion vacancies (such as oxygen and nitrogen vacancies) are shallow donors that favor n-type semiconductors (S. Wang, L. Pan, J.-J. Song, W. Mi, J.-J. Zou, L. Wang, X. Zhang, Titanium-defectedundoped anatase TiO2 with p-type conductivity, room-temperature ferromagnetism, and remarkable photocatalytic performance, J. Am. Chem. Soc., 137 (2015) 2975-2983). The formation of cation and anion vacancies in photocatalytic materials often results in "pn-junction"-like structures, which undergo significant exciton dissociation under the influence of the built-in electric field at the interface. Anion vacancies, due to their low binding energy, are considered common defects in transition metal oxides and have been extensively studied. Reports indicate that anion vacancies can positively influence photocatalytic performance by altering the electronic behavior, active surface sites, and band structure of semiconductor photocatalytic materials. N vacancies on photocatalysts (such as g-C3N4) generate lone pairs of electrons after the loss of N atoms, readily interacting with electron-rich substances or electron acceptors (G. Wang, Y. Zhao, H. Ma, C. Zhang, X. Dong, X. Zhang, Enhanced peroxymonosulfate activation on dual active sites of N vacancy modified gC(3)N(4) under visible-light assistance and its selective removal of organic pollutants, Sci. Total. Environ., 756 (2021) 144139). Compared to anion vacancies, metal cation vacancies have higher binding energies and are more difficult to design and manipulate.Due to their diverse orbital distributions and electronic configurations, metal cation vacancies play a crucial role in regulating the physicochemical properties and electronic structure of metal compounds (Y. Liu, H. Cheng, M. Lyu, S. Fan, Q. Liu, W. Zhang, Y. Zhi, C. Wang, C. Xiao, S. Wei, B. Ye, Y. Xie, Low Overpotential in vacancy-rich ultrathinCoSe2 nanosheets for water oxidation, J. Am. Chem. Soc., 136 (2014) 15670-15675). However, while the introduction of vacancies can enhance the catalytic activity of photocatalysts to some extent, as shallow carrier traps, their capture of carriers is instantaneous and cannot completely separate electrons and holes from space. Therefore, synergistic manipulation of the directional flow of carriers through co-catalyst interfacial coupling induced by anion and cation dual vacancies, thereby achieving spatial separation of electrons and holes, is an effective strategy.

[0004] MXene is an emerging two-dimensional cocatalyst with excellent electrical conductivity and numerous exposed metal sites on its surface, providing a possibility for the construction of metal vacancies. Taking the commonly used Ti3C2T as an example... xFor example, negatively charged Ti vacancies, acting as acceptor-type centers, can enhance photoelectric activity through unidirectional electron traps (Q. Dong, S. Ma, J. Zhu, F. Yue, Y. Geng, J. Zheng, Y. Ge, C. Fan, H. Zhang, M. Xiang, Q. Zhu, Ultrahigh mass activity for the hydrogen evolution reaction by anchoring platinum single atoms onactive {100} facets of TiC via cation defect engineering, Adv. Funct. Mater., 33 (2023) 2210665). Furthermore, as a cocatalyst coupled with semiconductor photocatalysts, Ti vacancies can not only precisely regulate photoinduced unidirectional electron transfer, but also provide more active sites for the adsorption of uranyl ions (X. Liu, F. Xu, Z. Li, Z. Liu, W. Yang, Y. Zhang, H. Fan, HY Yang, Design strategy for MXene and metal chalcogenides / oxides hybrids for supercapacitors, secondary batteries and electro / photocatalysis, Coordin. Chem. Rev., 464 (2022)214544). In hybrid systems, the synergistic effect of metal cation and anion vacancies can alter the charge distribution and enhance the hybridization effect. Therefore, the dual-vacancy-induced cocatalyst-enhanced hybridization strategy can achieve a synergistic effect on the photocatalytic reduction of U(VI). However, the promoting mechanism of the spatially separated cocatalyst induced by dual vacancy of anions and cations in the photocatalytic reduction of U(VI) is currently unclear. Summary of the Invention

[0005] This invention aims to provide a method for preparing and applying a heterogeneous photocatalyst. The invention synthesizes porous carbon nitride (CNv) containing defects using urea and thiourea as raw materials, and then reacts it with Ti3C2T... x MXene is mixed and then thermally etched with N2 to produce a composite material (CT) containing dual vacancies (N vacancies and Ti vacancies), which is then combined with MnO. x Coupling was used to prepare multiphase Ti3C2T xThe carbon nitride photocatalyst (CTM) is prepared by introducing dual vacancies. This not only alters the charge distribution on the photocatalyst surface and enhances the hybridization effect, but also provides more U(VI) adsorption sites, effectively overcoming the defect of weak surface charge in carbon nitride photocatalysts, which makes it difficult to capture U(VI). In particular, the dual vacancies can synergistically induce co-catalyst hybridization, enhancing the spatial separation of photoinduced charge carriers and visible light absorption, and promoting the accelerated accumulation of electrons and holes involved in redox reactions on the co-catalyst. The heterogeneous Ti3C2T prepared in this invention... x The photocatalyst possesses characteristics such as high charge space separation efficiency, fast charge transfer rate, good selectivity, strong photocatalytic reduction ability of U(VI), and good stability. Furthermore, the heterogeneous Ti3C2T prepared in this invention... x Photocatalysts have good reusability, are conducive to the sustainable development of the ecological environment, and have good application prospects.

[0006] This invention is achieved through the following technical solution: This invention provides a multiphase Ti3C2T x The preparation method of the photocatalyst includes the following steps: 1) Mix urea and thiourea, heat and stir. The resulting white crystalline powder is heated at 450-550 °C for 2-4 h. After cooling, the product is collected, washed and dried to obtain carbon nitride containing N defects. 2) Dissolve NH4F in hydrochloric acid, then add Ti3AlC2, stir at 40-60 °C for 24-48 h, separate the product, wash and dry to obtain Ti3C2T x MXene; 3) Combine the N-defect-containing carbon nitride obtained in step 1) with the Ti3C2T obtained in step 2). x MXene was mixed and heated at 450-550 ℃ for 2-4 h. The product was washed and dried to obtain carbon nitride containing two vacancies and Ti3C2T. x Composite materials; 4) Add K2MnO4 to the Mn(NO3)2 solution and mix thoroughly. React at 100-130 °C for 12-18 h, then cool to obtain the product MnO. x The carbon nitride containing two vacancies and Ti3C2T obtained in step 3) x Composite materials with MnO x The mixture was stirred in a solvent, and the product was washed and dried to obtain multiphase Ti3C2T. x Basic photocatalyst.

[0007] Further, the mass ratio of urea and thiourea in step 1) is 1:(1-4).

[0008] Further, in step 3), the N-defect-containing carbon nitride and Ti3C2Tx The mass ratio of MXene is (5-10):1.

[0009] Furthermore, the pH of the Mn(NO3)2 solution in step 4) needs to be adjusted to 3-4.

[0010] This invention also provides multiphase Ti3C2T obtained by the above preparation method. x Application of photocatalysts in the photocatalytic reduction of U(VI).

[0011] Furthermore, the multiphase Ti3C2T x The photocatalyst can selectively remove U(VI) under conditions of coexistence of multiple competing ions; the multiple competing ions include Y. 3+ La 3+ Ce 3+ Pr 3+ 、Nd 3+ 、Sm 3+ Eu 3+ Gd 3+ 、Tb 3+ Dy 3+ Ho 3+ Er 3 + Tm 3+ Yb 3+ Lu 3+ .

[0012] Furthermore, the multiphase Ti3C2T x Even after five adsorption / desorption cycles, the photocatalyst still achieved a U(VI) removal rate of over 93%.

[0013] Compared with the prior art, the beneficial effects of the present invention are: (1) The multiphase Ti3C2T synthesized in this invention x The method for developing a photocatalyst is simple, the structure is clear, and the stability is good.

[0014] (2) The multiphase Ti3C2T synthesized in this invention x In photocatalysts, the introduction of double vacancies not only changes the charge distribution on the surface of the photocatalyst and enhances the hybridization effect, but also provides more U(VI) adsorption sites.

[0015] (3) The multiphase Ti3C2T synthesized in this invention x The photocatalyst effectively overcomes the defect of weak surface charge of carbon nitride photocatalyst, which makes it difficult to capture U(VI). In particular, the dual-vacancy synergistic induced cocatalyst hybridization greatly enhances the spatial separation of photoinduced charge carriers and visible light absorption, and promotes the accelerated accumulation of electrons and holes participating in redox reactions on the corresponding cocatalyst.

[0016] (4) The multiphase Ti3C2T prepared by the present invention x Photocatalysts are reusable, which is beneficial to economic conservation and sustainable development of the ecological environment.

[0017] (5) The multiphase Ti3C2T prepared by the present invention x The photocatalyst exhibits good selectivity for U(VI) removal.

[0018] (6) The multiphase Ti3C2T prepared by the present invention x The photocatalyst exhibits rapid carrier transfer and good charge space separation performance, enabling efficient photocatalytic reduction of U(VI) and excellent selective removal. Attached Figure Description

[0019] Figure 1 Ti3C2T x A schematic diagram of the synthesis route for photocatalysts.

[0020] Figure 2 Ti3AlC2, Ti3C2T x PXRD patterns of PCN, CNv, CT, CTM and Ti3C2T (a) x Fourier transform infrared spectra of PCN, CNv, CT, and CTM (b).

[0021] Figure 3 Ti3C2T x N 1s XPS plot (a) and EPR plot (b) of PCN, CNv, CT and CTM.

[0022] Figure 4 The UV / Vis diffuse reflectance spectra of PCN, CNv, CT, and CTM are shown in (a) and their corresponding band gap diagrams in (b).

[0023] Figure 5 PL diagrams for PCN, CNv, CT, and CTM.

[0024] Figure 6 The diagram shows the photocatalytic kinetics (a) and photocatalytic rate constant (b) for PCN, CNv, CT, and CTM.

[0025] Figure 7 This is a graph showing the selectivity of CTM for the removal of U(VI) under UV / Vis irradiation.

[0026] Figure 8 This is a performance graph of CTM's cyclic usage.

[0027] Figure 9 It is Ti3C2T xA schematic diagram of the mechanism of photocatalytic reduction of U(VI) by a photocatalyst. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with embodiments. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0030] Example 1: Multiphase Ti3C2T x Preparation and characterization of photocatalysts 10 g of urea was placed in a porcelain boat and heated to 550 °C at a rate of 5 °C / min in a tube furnace. The reaction was carried out for 2 h. The product was washed repeatedly with ethanol and deionized water and then placed in a vacuum drying oven at 60 °C for 18 h to obtain pure g-C3N4 (PCN) in a light yellow color.

[0031] Dissolve 10 g of thiourea and 5 g of urea in 50 mL of deionized water and heat and stir at 80 °C until white crystalline powder is completely precipitated. Grind the obtained white crystalline powder thoroughly and heat it to 550 °C at a heating rate of 5 °C / min. Heat it in air for 2 h. Wash the product repeatedly with ethanol and deionized water, collect the solid material, and dry it in a vacuum drying oven at 60 °C for 18 h to obtain a yellow carbon nitride powder (CNv) containing N defects.

[0032] 3g of NH4F was added to a 37% HCl solution and dissolved by sonication. Then, Ti3AlC2 powder was slowly added to the solution, and the mixture was stirred slowly at 60 °C for 24 h. The resulting black product was obtained by centrifugation, repeatedly washed and centrifuged with ultrapure water until the pH of the filtrate reached neutral. Ethanol was then added and sonicated for 10 min. The black product was collected by centrifugation and vacuum dried to obtain Ti3C2T. x MXene; take 200 mg CNv and 20 mg Ti3C2T xMXene was mixed and thoroughly ground, and heated to 550 °C at a rate of 5 °C / min under N2 protection for 2 h. The solid was collected and repeatedly washed with ethanol and deionized water, and then dried in a vacuum oven at 60 °C for 18 h to obtain a grayish-green solid containing double-vacancy carbon nitride and Ti3C2T. x Composite materials (CT).

[0033] 2 g of Mn(NO3)2 was dissolved in 20 mL of deionized water, and 0.3 mol / mL sulfuric acid solution was slowly added dropwise while stirring to adjust the pH of the solution to 3-4. Then, 0.588 g of K2MnO4 was dissolved in deionized water and thoroughly mixed with the above-treated Mn(NO3)2 solution. The mixture was then poured into a reaction vessel and reacted at 120 °C for 12 h. After cooling to room temperature, the product was washed and dried to obtain black MnO. x Then MnO x Dispersed in N,N-dimethylformamide to prepare MnO x Solution. Finally, add 200 mg CT and 2 mg / mL MnO. x The solution was added to 30 mL of ethanol and stirred slowly for 6 h. The solid material was collected and dried in a vacuum drying oven at 60 °C for 18 h to obtain multiphase Ti3C2T. x CTM (Cyclic Photocatalyst).

[0034] Figure 1 Ti3C2T x A schematic diagram of the synthesis route for photocatalysts.

[0035] Figure 2 Ti3AlC2, Ti3C2T x PXRD patterns of PCN, CNv, CT, CTM and Ti3C2T (a) x Fourier transform infrared spectra of PCN, CNv, CT, and CTM (b). The crystal structure of the photocatalyst CTM was characterized by powder X-ray diffraction (PXRD). Figure 2 As can be seen, after etching, the Al characteristic peak at the 38.9° (104) plane of Ti3AlC2 disappears, and the 9.4° (002) plane shifts to a lower angle of 8.4°, indicating that Ti3C2T xMXene etching was successful. Furthermore, CNv exhibited two typical diffraction peaks at 13.1° and 27.4°, belonging to the (100) and (002) planes respectively, corresponding to the in-plane and interlayer stacking of the CNv heptazine ring units. However, compared to pure PCN, the intensity of these two diffraction peaks was significantly reduced after N2 heat treatment, indicating that N2 thermal etching weakened the interlayer stacking and generated more defects in the CNv structural units. The two typical diffraction peaks of the (100) and (002) planes were also observed in CT and CTM, while the Ti3C2T... x The small-angle characteristic peaks of MXene (002 plane) indicate the presence of CNv and Ti3C2T during the preparation of the photocatalyst CTM. x The crystal structure remains intact.

[0036] The chemical structure of the material was characterized using Fourier transform infrared spectroscopy. Figure 2 b can be seen at 800~810 cm -1 The characteristic absorption peak at 1000–1700 cm⁻¹ corresponds to the out-of-plane bending mode of the CNv heptamethrin ring. -1 The absorption band at 3000-3500 cm⁻¹ belongs to the stretching vibration of the aromatic CN heterocycle. -1 The characteristic peak at this point is attributed to the NH stretching vibration peak of the uncondensed amino group. CNv and Ti3C2T x MXene and MnO x The infrared spectrum of the composite CTM still retains the characteristic peaks of CNv, indicating that the photocatalyst CTM has been successfully prepared.

[0037] Figure 3 Ti3C2T x N 1s XPS plot (a) and EPR plot (b) of PCN, CNv, CT, and CTM. Figure 3 As can be seen, characteristic peaks at 404.2, 401.1, 398.8, and 399.8 eV appear in the N1s plot of PCN, which are attributed to π excitation and NH4+ excitation in the framework, respectively. x Group, bicoordinated N (CN=C, N) 2C ) and three-coordinate N(N-3C, N 3C Compared to PCN, the binding energy of N-3C in CNv is slightly lower by ~0.3 eV, which is due to the adjacent N vacancies in the CNv structure. In other materials containing N vacancies, the proportion of N-3C area is significantly increased, indicating the generation of more N defect sites. In CNv and Ti3C2T... x After MXene hybridization, the N1s binding energy of CT shifts to higher fields, indicating that Ti3C2T xMXene interacts with CNv, resulting in a decrease in the electron density of N in CNv. Figure 3 As can be seen from b, a sharp EPR signal appeared on CT and CTM at ~1.97, indicating the generation of more Ti vacancies. However, with MnO x The addition of MnO weakened the signal, which may be due to the presence of MnO. x The particles occupy the Ti vacancies, reducing the amount of unpaired electrons on the charge carriers. Furthermore, a characteristic peak for N vacancies is observed at g=2.003, which can be attributed to the spn in the π-conjugated aromatic ring. 2- Carbon atoms generate the same type of lone pair electrons. The N-vacancy EPR signals of CNv, CT, and CTM are significantly stronger than those of the original g-C3N4, indicating that more unpaired electrons are formed due to the introduction of N vacancies. The absence of N atoms on the triazine ring generates a large number of extra electrons, which will be redistributed to neighboring carbon atoms through delocalized conjugation, forming additional unpaired electrons.

[0038] Figure 4 The UV / Vis diffuse reflectance spectra (a) and corresponding bandgap diagrams (b) for PCN, CNv, CT, and CTM are shown. Figure 4 As can be seen, the absorption edge of pure PCN is at 447 nm. When double vacancies are introduced, the absorption edge redshifts and extends to 521 nm. Compared to PCN, CNv and CT form new absorption bands, which can be attributed to the n→π* electronic transitions (N-vacancies and Ti-vacancies) caused by lone pairs of electrons at the defect sites. These results indicate that the introduction of double vacancies jointly optimizes the electronic structure and improves the utilization of visible light. Furthermore, Ti3C2T... x MXene exhibits a broad absorption band (200-800 nm), which is due to Ti3C2T x The black color of MXene is due to its color. The band gaps (Eg) calculated using the Kubelka-Munk (KM) transform are 2.81, 2.68, 2.55, and 2.41 eV, respectively. Figure 4 b). The introduction of double vacancies reduces the optical band gap because the absence of N and Ti atoms alters the band structure. Figure 5 PL diagrams for PCN, CNv, CT, and CTM. (By...) Figure 5 It is evident that the generation of N and Ti vacancies in the steady-state photoluminescence (PL) spectrum leads to a gradual decrease in PL intensity, with the lowest PL intensity observed in CTM. This indicates that the synergistic induction of cocatalyst hybridization by the two vacancies effectively promotes photoinduced carrier separation.

[0039] Example 2: Photocatalytic reduction kinetics of U(VI) by CTM 5 mg CTM was dispersed in 20 mL of a solution containing 100 ppm U(VI) (pH 5). Under dark conditions, the suspension was shaken for 120 minutes to reach adsorption-desorption equilibrium. Then, the solution was irradiated with a xenon lamp. At set time intervals, a certain amount of the supernatant was collected, filtered through a 0.22 μm polyethersulfone membrane, and the residual concentration of U(VI) in the solution was determined by ICP-MS. The photocatalytic reaction rate constant was expressed as -ln(C e The removal rate R of U(VI) is calculated by R = (C0 - C) = k. e ) / C0×100% is calculated, where C e C0 and C0 represent the equilibrium concentration and the initial U(VI) concentration, respectively, and the constant k represents the reaction rate constant min. -1 .

[0040] Figure 6 Photocatalytic kinetics (a) and photocatalytic rate constant (b) of PCN, CNv, CT, and CTM are shown. Figure 6 As can be seen, the presence of dual vacancies significantly enhances the photocatalyst's ability to reduce U(VI). Compared to CNv's 57.9% removal rate of U(VI), CT's removal rate of U(VI) increased to 80.7%, which is due to the Ti3C2T x The negative charge on the MXene surface contributes to this. Furthermore, the formation of Ti vacancies provides more active sites, thus facilitating U(VI) anchoring. CTM achieved a U(VI) removal rate of up to 96.1% after 90 min of illumination. The photocatalytic reaction rate constant k of different photocatalysts was evaluated using a pseudo-first-order reaction kinetic model. Figure 6 As can be seen, the photoreaction rate constant k of CTM is 8.5 times, 4.9 times, and 2.4 times that of PCN, CNv, and CT, respectively, indicating that CTM has significant photocatalytic activity for the photocatalytic reduction of U(VI).

[0041] Example 3: Selectivity of CTM photocatalytic reduction of U(VI) Tailings waste liquid contains a large number of coexisting ions, such as: Y 3+ La 3+ Ce 3+ Pr 3+ 、Nd 3+ 、Sm 3+ Eu 3+ Gd 3+ 、Tb 3+ Dy 3+ Ho 3+ Er 3+ Tm 3+ Yb 3+ Lu 3+The selectivity of CTM for U(VI) removal was investigated under the conditions of pH 5 and a U(VI) to interfering ion concentration ratio of 1:5. 5 mg of CTM was dispersed in 20 mL of mixed ion solution, and the solution was shaken at 150 rpm for 8 h under xenon lamp irradiation. After standing, the supernatant was collected and filtered through a 0.22 μm polyethersulfone membrane. The residual concentration of U(VI) in the solution was determined by ICP-MS.

[0042] Figure 7 This is a graph showing the removal selectivity of CTM for U(VI) under UV / Vis irradiation. Figure 7 It is evident that CTM still exhibits excellent photocatalytic efficiency for U(VI) even with 5 times the coexistence of rare earth ions.

[0043] Example 4: Reusability of CTM 5 mg of CTM was dispersed in 20 mL of a solution containing 20 ppm U(VI) to complete the first photocatalytic reduction experiment. The photocatalyzed CTM material was collected and soaked and stirred in 100 mL of NaHCO3 (0.1 M) solution for 6 h. The CTM material was then washed 3-5 times with 1 wt% HNO3 and deionized water and then vacuum dried for the next photocatalytic experiment. Figure 8 This is a performance graph of CTM's cyclic usage. (By...) Figure 8 It is evident that after five cycles, CTM still maintains excellent photocatalytic activity, with a U(VI) removal rate as high as 93.2%.

[0044] Figure 9 It is Ti3C2T x A schematic diagram of the photocatalytic reduction mechanism of U(VI) by the photocatalyst. The mechanism of photoreduction of U(VI) to U(IV) and the flow of photogenerated charges at the CTM interface can be explained as: UO2 2+ First, it adsorbs onto the CTM surface or anchors to vacancies. Under visible light irradiation, CNv containing N vacancies generates electrons and holes, and electrons in VB are excited to CB. Then, electrons in the CNv conduction band are excited by Ti3C2T. x MXene migrates to Ti3C2T at a lower Fermi level. x MXene drives the reduction of U(VI) to generate U(IV). Because the CB potential of CTM (-1.38 V) is higher than that of E(O2 / ·O2),... - (-0.33 V vs NHE) is more negative, with some electrons reacting with dissolved oxygen in the water to generate O2. -This further promotes the reduction of U(VI) to U(IV). Additionally, electrons may be trapped by unsaturated covalent bonds near N vacancies. However, since the nitrogen defect level is shallow, the electron trapping process is transient. Holes remaining in VB are then transferred to MnO. x Because of the high electron density around Ti vacancies in MXene, these holes can be captured by Ti vacancies. At the same time, the captured holes react with dissolved oxygen in the water to generate O2, achieving spatial separation of electrons and holes.

[0045] The embodiments described above are merely preferred embodiments of the present invention, and while the descriptions are specific and detailed, they are not intended to limit the present invention. It should be noted that various changes and modifications can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the concept and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A multiphase Ti3C2T x The preparation method of the photocatalyst is characterized by, Includes the following steps: 1) Mix urea and thiourea, heat and stir, and heat the resulting white crystalline powder at 450-550 °C for 2-4 h. Cool and collect the product, wash and dry it to obtain carbon nitride containing N defects; the mass ratio of urea to thiourea is 1:(1-4). 2) Dissolve NH4F in hydrochloric acid, then add Ti3AlC2, stir at 40-60 °C for 24-48 h, separate the product, wash and dry to obtain Ti3C2T x MXene; 3) Combine the N-defect-containing carbon nitride obtained in step 1) with the Ti3C2T obtained in step 2). x MXene was mixed and heated at 450-550 ℃ for 2-4 h. The product was washed and dried to obtain carbon nitride containing two vacancies and Ti3C2T. x The composite material; the carbon nitride containing N defects and Ti3C2T x The mass ratio of MXene is (5-10):1; 4) Add K2MnO4 to the Mn(NO3)2 solution and mix thoroughly. React at 100-130 °C for 12-18 h, then cool to obtain the product MnO. x The carbon nitride containing two vacancies and Ti3C2T obtained in step 3) x Composite materials with MnO x The mixture was stirred in a solvent, and the product was washed and dried to obtain multiphase Ti3C2T. x Mn(NO3)2 solution is a photocatalyst; wherein the pH of the Mn(NO3)2 solution needs to be adjusted to 3-4.

2. The multiphase Ti3C2T obtained by the preparation method of claim 1 x Application of photocatalysts in the photocatalytic reduction of U(VI).

3. The application according to claim 2, characterized in that, The multiphase Ti3C2T x The photocatalyst can selectively remove U(VI) under conditions of coexistence of multiple competing ions; the multiple competing ions include Y. 3+ La 3+ Ce 3+ Pr 3+ 、Nd 3+ 、Sm 3+ Eu 3+ Gd 3+ 、Tb 3+ Dy 3+ Ho 3+ Er 3+ Tm 3+ Yb 3+ Lu 3+ .

4. The application according to claim 2, characterized in that, The multiphase Ti3C2T x Even after five adsorption / desorption cycles, the photocatalyst still achieved a U(VI) removal rate of over 93%.

Citation Information

Patent Citations

  • Difunctional M / Ti3C2Tx / Zn3In2S6 composite photocatalyst as well as preparation method and application thereof

    CN117463383A